The Theatre of the Street: Public Violence in Antwerp During the First Half of the Twentieth Century - Vrints, Antoon (Crime and City in History, 2019)
In The Theatre of the Street: Public Violence in Antwerp During the First Half of the Twentieth Century Antoon Vrints offers a historical analysis of the meanings and functions of street violence in a modern European city.